Resilience and degradation in a tropical wetland overgrazed by cattle - Santos, Sandra A.; Perotto-Baldivieso, Humberto L.; Young, Dylan (Cranfield University, 2014)
INTRODUCTION: The Pantanal, one of the largest wetlands in the world, has a great diversity of flora and fauna. The dynamic hydrological regime, combined with heterogeneous to-pography, has resulted in a mosaic of diverse habitat types in terms of species and physical structure. Due to the abundance of forage resources, the Pantanal flood-plains are important for beef cattle production. Cattle prefer grazing near water bodies because these areas have high quality forage as a result of flooding regimes (Santos et al. 2002). Many wetlands go through a wet/dry cycle that is essential to maintain their produc-tivity and function. In drier years, wetland drawdown provides optimal conditions for a diverse range of forage species, and cattle can graze continuously, leading to pasture degradation. It is therefore essential to under-stand the spatial and temporal dynamics of forage production and consumption. In this study we assessed and monitored vegetation at the edge of one of the pond habitats intensively grazed by cattle, in order to evaluate degradation and quantify indicators of resilience (Briske et al. 2006).